Do Creatinine Blood Levels Act upon Fatty Acid Metabolites in Human Red Blood Cell Membranes? - Giuseppe, Gallo; Guglielmo, Martino (Free Radicals and Antioxidants)
Objectives: The aim of the present research is to correlate creatininemia and uricemia to HNE and MDA levels of Red Blood Cell purified membranes in comparison to those of normal subjects to characterize the effects of oxidative stress. Methods: The studied population consisted of 10 patients with endogenous both hypercreatininemic hyperuricemic and ten normal subjects. The measurement of total proteins in RBC ghosts and HNE and MDA are conducted on blood samples of patients. Results: The obtained data evidence that both creatinine and uric acid levels have influence on the ratio of both MDA/protein and HNE/protein content on RBC ghosts, demonstrating their possible protective role against oxidative stress at low concentrations in blood and oxidizing power at higher concentrations. Conclusion: The displayed results in this study suggest that at low concentrations of creatinine and uric acid there is oxidative stress in human erythrocyte membrane, but if creatinine and uric acid have slowed down to sufficient limits there is also oxidative stress, as demonstrated by MDA and HNE levels; only if the concentration of these two substances overwhelms a threshold.
Keywords: Oxidative stress; Creatininemia; Uricemia; Red blood cell; Cytoplasmic membranes